A Nanotechnology-Green Synthesis of Nanoparticles for the Treatment of Alzheimer Disease - Anuja K U,; Hemnath Elango,; Jilsha G,; Jayesh V N,; Vineeth V S, (The Bioscan, 2024)
Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterised by cognitive decline and memory loss. The exact cause of the disease is unknown; however, a combination of genetic, environmental, and lifestyle factors is believed to contribute to its onset. Aim: Nanotechnology-Green Synthesis of Nanoparticles for the Treatment of Alzheimer Disease. Methodology: The study examined the anti-Alzheimer's activity of various biogenically synthesized nanoparticles, focusing on their mechanisms, stability, and specific targeting attributes. Data was gathered from patent databases, conference abstracts, publications, and Google searches, concluding October 31, 2022. Results: Genetic predisposition and family history of Alzheimer's increase risk, while environmental factors like toxins and head injuries can also heighten the risk. The disease is characterised by a deficiency in neurotransmitters, particularly acetylcholine, and the accumulation of abnormal proteins in the brain, such as beta-amyloid plaques and tau tangles, which disrupt communication between nerve cells and contribute to cognitive impairment .Chronic inflammation of the brain, vascular issues, and impaired energy metabolism in brain cells also contribute to disease complications. The emotional and economic burden of Alzheimer's is significant and there is an urgent need for effective interventions and support systems to alleviate its impact on individuals, caregivers, and society. Nanotechnology has emerged as a promising field, with diverse applications across various domains that contribute to human welfare. Nanoparticles have unique physical and chemical properties that make them invaluable for various applications, including the early detection of life-threatening disorders such as cancer, Alzheimer's disease, and bioremediation. The eco-friendly synthesis of metallic nanoparticles using green synthesis methods is a promising approach to avoid the generation of harmful byproducts. Conclusion: AD is a neurodegenerative disorder influenced by genetics, environmental factors, and biology. Nanotechnology offers innovative treatments, including nanoparticles that address the blood-brain barrier, demonstrating its potential to revolutionize therapeutic approaches.